EVALUASI PENERAPAN METODE VALUE ENGINEERING DALAM PENINGKATAN KUALITAS KONSTRUKSI - Anugrah Ramadha Pratama (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The construction industry is required to produce cost-efficient projects without compromising the quality and function of the building. One method that can be applied to achieve this goal is Value Engineering (VE), a systematic approach focused on increasing value through functional and cost analysis. This study aims to evaluate the application of Value Engineering methods in improving construction quality. The research method used is descriptive qualitative, using a literature study and analysis approach to the application of Value Engineering to construction projects. Data were obtained from various library sources, project documents, and evaluation results of VE implementation. The results show that the application of Value Engineering can produce more efficient design alternatives and implementation methods without compromising construction quality. Furthermore, this method contributes to improved building function, more optimal material selection, and project cost efficiency. Therefore, it can be concluded that Value Engineering is an effective method for improving construction quality and overall project value